Transformed extracellular vesicles with high angiogenic ability as therapeutics of distal ischemic tissues - Ngo, Nhat-Hoang; Chang, Yun-Hsuan; Vuong, Cat-Khanh; Yamashita, Toshiharu; Obata-Yasuoka, Mana; Hamada, Hiromi; Osaka, Motoo; Hiramatsu, Yuji; Ohneda, Osamu (Frontiers in Cell and Developmental Biology, 2022)
Introduction: The therapeutic effects of endothelial progenitor cells (EPC) in neovascularization have been suggested; however, to date, few studies have been conducted on the ability of EPC-derived extracellular vesicles (EV) to rescue the ischemic tissues. In order to examine the functional sources of EV for cell-free therapy of ischemic diseases, we compared the functions of EPC-EV and those from Wharton’s Jelly-derived mesenchymal stem cell (WJ-EV) in the flap mouse model. Results and Conclusion: Our results demonstrated that in the intravenous injection, EPC-EV, but not WJ-EV, were uptaken by the ischemic tissues. However, EPC-EV showed poor abilities to induce the neovascularization and the recovery of ischemic tissues. In addition, compared to EPC-EV, WJ-EV showed the higher ability to rescue the ischemic injury when being locally injected to the mice. In order to induce the secretion of a high functional EPC-EV, EPC were internalized with hypoxic pretreated WJ-EV, which resulted in a transformed hwEPC. In comparison to EPC, hwEPC showed the induced proliferation, the upregulation of angiogenic genes and miRNAs, and the promoted angiogenic ability. Interestingly, hwEPC produced a modified EV (hwEPC-EV) that highly expressed miRNAs related to angiogenesis, such as miR-155, miR-183, and miR-296. Moreover, hwEPC-EV significantly induced the neovascularization of the ischemic tissues which were involved in promoting the proliferation, the expression of VEGF and miR-183, and the angiogenic functions of endothelial cells. Of note, hwEPC-EV were higher uptaken by the ischemic tissues and showed the greater effect with regard to inducing recovery from ischemic injury in the intravenous administration, compared to EPC-EV. Therefore, hwEPC-EV can be considered as a functional candidate for cell-free therapy to treat the distal ischemic tissues.